2010
DOI: 10.1123/ijsnem.20.5.427
|View full text |Cite
|
Sign up to set email alerts
|

Water and Solute Absorption From Carbohydrate-Electrolyte Solutions in the Human Proximal Small Intestine: A Review and Statistical Analysis

Abstract: The purpose of this study is to summarize water, carbohydrate (CHO), and electrolyte absorption from carbohydrate-electrolyte (CHO-E) solutions based on all of the triple-lumen-perfusion studies in humans since the early 1960s. The current statistical analysis included 30 reports from which were obtained information on water absorption, CHO absorption, total solute absorption, CHO concentration, CHO type, osmolality, sodium concentration, and sodium absorption in the different gut segments during exercise and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 87 publications
0
38
0
Order By: Relevance
“…The characteristics of upper intestinal water and electrolyte absorption are similar in rabbits (Love et al 1965), dogs (Bilchik et al 1994), sheep (Hyun et al 1995) and humans (Gisolfi et al 1988; Shi & Passe, 2010). Therefore, while upper intestinal water, electrolyte and glucose absorption remains to be adequately characterized in horses, the similarities amongst other monogastrics and sheep provides the basis for the supplement design and experimental design used in the present study.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The characteristics of upper intestinal water and electrolyte absorption are similar in rabbits (Love et al 1965), dogs (Bilchik et al 1994), sheep (Hyun et al 1995) and humans (Gisolfi et al 1988; Shi & Passe, 2010). Therefore, while upper intestinal water, electrolyte and glucose absorption remains to be adequately characterized in horses, the similarities amongst other monogastrics and sheep provides the basis for the supplement design and experimental design used in the present study.…”
Section: Methodsmentioning
confidence: 99%
“…The standard electrolyte solution consisted of 32 g dissolved per litre of water to give the following measured (Nova Statprofile 5 blood gas and ion analyzer; Nova Biomedical, Waltham, MA, USA) concentrations (in mmol l −1 ): glucose, 31; Na + , 65.3; K + , 27.0; Cl − , 84.6; and Ca 2+ , 2.11; with a [HCO 3 − ] of 2.2 mmol l −1 , pH 7.43 and osmolarity of ∼220 mosmol l −1 . The lower than plasma concentration for Na + is to keep the osmolarity lower than body fluids so as to facilitate both gastric emptying and intestinal absorption of the solution, as has been shown in humans (Shi & Passe, 2010), and to minimize concerns about palatability of salty solutions. Solutions of high osmolarity are associated with slowed gastric emptying, less than optimal water and ion absorption rates, net water flux into the upper intestine and gastrointestinal upset in humans (Shi & Passe, 2010), and it was most desirable to avoid these complications.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although some differences between individual studies remain that might be explained in part by differences in total solute and carbohydrate composition, Shi and Passe (2010) concluded by statistical metaregression that overall osmolality plays a significant role in water absorption in the duodenojejunum. They found that solutions containing single carbohydrates have a higher negative correlation with water absorption than solutions containing multiple transportable carbohydrates (e.g., glucose, fructose, sucrose) and that this effect is greatest in the jejunum, with the negative correlation disappearing.…”
Section: Discussionmentioning
confidence: 99%
“…It does not appear that CHO ingestion simply exceeded the maximal rate of CHO absorption and/or oxidation of the participants, as in this case a similar intermittent endurance capacity between the HCHO and MCHO trials would have been expected. This requires further study, perhaps by focussing initially on potential modulators of CHO exo oxidation (Jeukendrup 2004;Shi and Passe 2010). However, it should also be noted that there was a larger variation in time to exhaustion values for the HCHO trial, perhaps representing a greater individual variation in response to this CHO dose.…”
Section: Time To Exhaustionmentioning
confidence: 94%